Mechanism of dact2 gene inhibiting the occurrence and development of liver fibrosis - Huang, Shen’an; Qian, Xia; Jiang, Ting; Xiao, Jing; Yin, Min; Xiong, Ming; Wen, Zhili (Cellular and Molecular Biology, 2022)
There are few reports about the relationship between dact2 and liver fibrosis. The inhibitory mechanism of dact2 in liver fibrosis is not clear, we need to further explore it. In this study has been shown that the dact2 gene can inhibit liver fibrosis. In this experiment, we used lentivirus as a vector to construct a lentivirus vector carrying the dact2 gene and packaged dact2 recombinant lentivirus and its control vector. HSC-T6 infected cells were observed. The effect of dact2 gene expression was activated by Wnt3a HSC-T6 cells. Immunoblot was used to detect α - SMA expression, TGF - β 1, Smad3, Smad7, β - Catenin and CyclinD1. The expression of MMP-2 and TIMP-1 was detected by real-time PCR. At the same time, dact2 recombinant lentivirus was injected into the tail vein. Carbon tetrachloride was used to establish the liver fibrosis model. After 7 weeks of modeling, the staining was used to observe the pathological changes of liver tissue, hydroxyproline was used to analyze the changes of collagen content in liver tissue, the expression of the protein was observed by immunohistochemistry, and the expression of fibrosis-related genes was detected by real-time PCR. Results showed that the dact2 gene expression could inhibit the activation of HSC-T6 cells and reduce the expression of TGF - β 1. The percentage of Smad3, β - Catenin and cyclinD1 protein was 50.02%, 46.73%, 47.58% and 37.50% respectively (P < 0.05).